community engagement and service learning in a south african university: the challenges of adaptive leadership - Preece, Julia (South African Journal of Higher Education, 2016)
This article presents the preliminary findings of two community engagement/service learning case studies undertaken at one South African university. The following criteria were used for selecting the case studies: they were community needs-led, attracted a multidisciplinary team approach and involved service learning students from different disciplines. The findings highlight the challenges of negotiating these three dimensions, and the perceived learning benefits for community, staff and student participants. The article draws on service learning and community engagement literature which highlights the paucity of research regarding multidisciplinary engagement or the community voice in service learning projects. It frames its discussion around theories of community development, with reference to the concepts of adaptive leadership and collaboration. It concludes by stating that small-scale projects can demonstrate mutually beneficial outcomes for all partners but that communication and leadership are multi-layered, requiring university vigilance in relation to competing values and purposes. KEYWORDS Adaptive leadership, asset-based development, community engagement